Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kota Padang - Aulia Fitri Tsuraya; Jhon Fernos (Jurnal Publikasi Ilmu Manajemen, 2023)
This research was conducted to determine the effect of work motivation variables and work discipline variables on the performance of employees of the Padang City Population and Civil Registration Service. companies that operate in the field of community service. The population in this study were all employees of the Padang City Population and Civil Registration Service. The sample in this study totaled 45 employees or respondents at the Padang City Population and Civil Registration Service. 45 employees. In this study the types of data used were primary data and secondary data. Research data were analyzed using multiple linear regression analysis techniques and statistical t tests. Research data were collected from the results of respondents and analyzed with linear regression and hypothesis testing. Results of analysis This study shows that work motivation has a positive and significant effect on employee performance at the Padang City Population and Civil Registration Office with a t-count of (5.051 > 2.019), and work discipline has a positive and significant effect on employee performance at the Padang City Population and Civil Registration Service with t-count of (4.345 > 2.019).